Preventing birth defects, saving lives, and promoting health equity: an urgent call to action for universal mandatory food fortification with folic acid - Vijaya Kancherla, PhD; Lorenzo D Botto, MD; Laura A Rowe, MPH; Nathan A Shlobin, BA; Adrian Caceres, MD; Anastasia Arynchyna-Smith, MPH; Kathrin Zimmerman, BA; Jeffrey Blount, MD; Zewdie Kibruyisfaw, MD; Kemel A Ghotme, MD; Santosh Karmarkar, MCh; Graham Fieggen, MD; et al. (Elsevier, 2022)
Summary: July 20, 2021 marked the 30th anniversary of the publication of the landmark trial by the British Medical Research Council showing unequivocally that maternal intake of folic acid (vitamin B9) starting before pregnancy prevents most cases of infant spina bifida and anencephaly-two major neural tube defects that are severe, disabling, and often fatal. Mandatory food fortification with folic acid is a safe, cost-effective, and sustainable intervention to prevent spina bifida and anencephaly. Yet few countries implement fortification with folic acid; only a quarter of all preventable spina bifida and anencephaly cases worldwide are currently avoided by food fortification. We summarise scientific evidence supporting immediate, mandatory fortification with folic acid to prevent the development of spina bifida and anencephaly. We make an urgent call to action for the World Health Assembly to pass a resolution for universal mandatory folic acid fortification. Such a resolution could accelerate the slow pace of spina bifida and anencephaly prevention globally, and will assist countries to reach their 2030 Sustainable Development Goals on child mortality and health equity. The cost of inaction is profound, and disproportionately impacts susceptible populations in low-income and middle-income countries.